Penerapan Media Pembelajaran Berbasis Website Canva untuk Meningkatkan Minat Literasi Siswa SMP/MTs - Tazqiyatul Fithriya; Latifatul Mosyarofah; Heny Sulistyowati; Fitri Resti Wahyuniarti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2026)
ABSTRACT This study aimed to develop and implement a Canva-based learning website to improve students’ literacy interest and skills. The research employed a Research and Development (R&D) method, including needs analysis, design, product development, expert validation, revision, limited trials, and field trials. Research instruments consisted of validation questionnaires, observations, interviews, and literacy tests. The validation results indicated that the learning media were categorized as highly feasible, with scores of 89% from content experts, 92% from media experts, and 88% from language experts. The trial results showed an increase in students’ literacy interest, with the average score rising from 63 to 84. Reading skills improved from 68 to 85, while writing skills increased from 65 to 83. Observations and interviews further confirmed that the Canva-based website enhanced students’ activeness, independence, and self-confidence in literacy activities. Therefore, the Canva-based learning website proved to be feasible and effective in improving students’ literacy interest and skills comprehensively. Keywords: Canva-basedW; Reading Literacy; Writing Literacy; Digital Learning Media; Learning Motivation